Controls on Yardang Development and Morphology: 1. Field Observations and Measurements at Ocotillo Wells, California. Issue 4 (26th April 2018) - Pelletier, Jon D.; Kapp, Paul A.; Abell, Jordan; Field, Jason P.; Williams, Zachary C.; Dorsey, Rebecca J.
Abstract: Yardangs are streamlined hills formed in part by the erosive action of wind and wind‐blown sediments. Here we examine the controls on yardang development and morphology using the Ocotillo Wells State Vehicular Recreation Area (OWSVRA), California, as a study site. We measured the compressive strengths, strikes, and dips of bedrock strata, eolian sediment fluxes (including their vertical profiles and spatial variations around yardangs), and erosion rates derived from geologic constraints and multitemporal Terrestrial Laser Scanning (TLS). We used a combination of TLS‐based and airborne lidar‐based Digital Elevation Models (DEMs) to test the applicability of an asymmetric Gaussian function for characterizing yardang form and quantify the relationships among yardang lengths, widths, heights, spacings, and their controlling factors. Yardang aspect ratios are controlled by bedrock structural attributes, specifically by the tangent of the dip and the angle between the strike and the prevailing wind direction. Yardang spacings scale linearly with yardang width. Yardang heights increase as the square root of width such that larger yardangs tend to have gentler side slopes. Sediment fluxes reach a maximum in the troughs among yardangs, consistent with the hypothesis that yardang development involves the focusing of wind and wind‐blown sediments into troughs. The vertical distribution of eolian sediment flux follows a power law with an exponent of −2.5, a result consistent with an advection‐diffusion‐settling model of transport near the saltation‐suspension transition. Erosion rates are several mm/yr over time scales of ~10 0 and ~10 6  years. Key Points: Yardang morphology at the study site is controlled by bedrock structure Sediment flux is near saltation‐suspension transition and highest in troughs Erosion rates are several mm/yr over time scales of ~10 0 and ~10 6  years